Estimation of breeding value and genetic trend of Garut sheep and its crossbred - Ismeth Inounu; Subandriyo .; E Handiwirawan; L.O Nafiu (Jurnal Ilmu Ternak dan Veteriner, 2007)
Crossing of Garut (GG) sheep with St. Croix sheep (HH) and Moulton Charollais (MM) resulting HG sheep (♂HH X ♀GG) and MG sheep (♂MM X ♀GG) was done by Indonesian Research Institute for Animal Production. The work continued by crossing MG and HG sheep to obtain HMG (♂HG X ♀MG) and MHG (♂MG X ♀HG) sheep. The study was continued by selection program based on phenotypic performance. Estimation of breeding value and genetic trends were done in order to study the effectiveness of selection program and to study the genetic progress of each breed. The breeding value was estimated by Best Linear Unbiased Prediction (BLUP) method using Variance Component Estimation (VCE4) software to calculate variance component and using Prediction and Estimation (PEST) to calculate Breeding Value. Genetic variations of composite sheep were generally higher than Garut sheep, represented by higher estimated heritability value. Genetic correlation of body weight at diffrent age is high, that makes selection at one age could also increase body weight at any level of age. In general of this population shows positive genetic trend, but fluctuated from year to year. Composite breed tend to have higher estimated breeding value than Garut sheep. Selection method that was practiced in this population showed in line with selection method using breeding value criteria. Key Words: Breeding Value, Genetic, BLUP, Garut Sheep, St. Croix, Moulton Charollais